Modelling Experiences And Its Factors In General Mathematics: The Case Of Grade 11 Students - Leomarich F Casinillo; Emily L Casinillo (Universitas Pendidikan Ganesha, 2020)
Student’s experiences in learning plays an essential role in producing quality academic achievement. This study aimed to develop multiple regression models on the students’ experiences in learning mathematics in regards to its influencing factors. A simple random sampling of 112 grade 11 students in the first semester of school year 2018-2019 from Visayas State University were used as the respondents of this study. Result of the study reveals that grade 11 students’ learning experience in general mathematics is challenging and logical. However, it is found out that it is satisfying and rewarding since it develops their critical thinking and decision making in real life. The number of hours in studying and studying with internet positively influence the students’ learning experience in mathematics. It is also revealed that STEM students are more fond learning mathematics compare to non-STEM students. Furthermore, result also shows that a conducive learning environment and religious activities in the campus helps the students to have a peaceful and positive learning experience.